School performance in three South East Asian countries: lessons in leadership, decision-making and training - Gill, C. M. H. D. *; Berezina, E * (Emerald, 2020)
Purpose: The three neighbouring nations of Indonesia, Malaysia and Singapore participated in the 2009, 2012 and 2015 Programme for International Student Assessment (PISA) cycles. Despite many similarities between the three nations, Singapore has consistently been a top PISA performer, with Malaysia and Indonesia in the bottom third of the international league tables. This paper aims to sketch the comparative Association of South East Asian Nations (ASEAN) context and uses PISA-derived metrics to contrast how differences in decision-making and school leadership, particularly in relation to staff development and training practices, may impact school performance across Indonesia, Malaysia and Singapore. Design/methodology/approach: Ten scales from the 2015 PISA School Questionnaire for Malaysia, Singapore and Indonesia were analysed using ANOVA and t-tests as an aid to exploring the extent to which different approaches to teacher training, school leadership and governance may impact student performance. Findings: Although Malaysian and Indonesian school principals report higher levels of autonomy than Singaporean peers, other evidence suggests that schools in Singapore may actually have greater decision latitude. Most significantly, Singaporean teachers take responsibility for key staff development decisions and skills transfer, whereas in Indonesia and Malaysia, teacher training is controlled by government administrators, a factor that may be a critical differentiator between the school systems. Practical implications: In Singapore, teacher training is controlled by and for teachers through professional learning teams within schools and professional learning communities across schools; in Malaysia and Indonesia, similar decisions are taken by external administrators. Giving Malaysian and Indonesian teachers control over their own training could be a simple and powerful reform to target skills gaps and to generalise improvements in pedagogy quickly across schools and thus to lift school performance in these countries. Originality/value: This paper highlights how differences at systemic and school levels, particularly in approaches to teacher training and leadership and may explain differentials in school performance in three ASEAN education systems.